2003
DOI: 10.1161/01.hyp.0000073581.74107.22
|View full text |Cite|
|
Sign up to set email alerts
|

Influence of Vitamin C on Baroreflex Sensitivity in Chronic Heart Failure

Abstract: Abstract-Chronic heart failure (CHF) reduces baroreflex sensitivity. Low baroreflex sensitivity, a risk factor for sudden death, could arise partly from CHF-dependent endothelial dysfunction. Vitamin C at high doses has a protective role against CHF-related endothelial damage. This study was conducted to investigate the effect of vitamin C on baroreflex sensitivity in CHF. A study group of 33 subjects with CHF secondary to postischemic dilated cardiomyopathy with an ejection fraction Յ35% and a control group (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
36
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 53 publications
3
36
0
2
Order By: Relevance
“…These data suggest a direct suppressive action of reactive oxygen species on carotid baroreceptors. Moreover, acute intravenous infusion of ascorbic acid increases cardiovagal BRS in patients with congestive heart failure (27,28). Importantly, administration of antioxidants in these previous investigations, as well as in the present study, had no effect on baroreflex function in healthy young controls (22,27), suggesting that ascorbic acid administration in the absence of oxidative stress has no influence on cardiovagal BRS.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…These data suggest a direct suppressive action of reactive oxygen species on carotid baroreceptors. Moreover, acute intravenous infusion of ascorbic acid increases cardiovagal BRS in patients with congestive heart failure (27,28). Importantly, administration of antioxidants in these previous investigations, as well as in the present study, had no effect on baroreflex function in healthy young controls (22,27), suggesting that ascorbic acid administration in the absence of oxidative stress has no influence on cardiovagal BRS.…”
Section: Discussionsupporting
confidence: 49%
“…Depressed cardiovagal responsiveness has been linked to impaired BP regulation with aging (32) and an increased incidence of sudden cardiac death in patients with coronary artery disease (19,20). Thus the identification of mechanisms underlying depressed cardiovagal BRS has important clinical implications.Many cardiovascular disease states are associated with baroreflex impairment (4, 10), with oxidative stress playing a possible mechanistic role (22,27,28). Aging, which is a primary risk factor for cardiovascular disease development (21), is associated with a reduction in cardiovagal BRS (9, 13, 25) and increased levels of oxidative stress (15,17,18,40).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, we also showed that ascorbic acid could significantly attenuate the increase in blood pressure during hyperglycemia. Because ascorbic acid does not have hypotensive properties in healthy, disease-free individuals (7,32,34,51,52), it is therefore evident that ascorbic acid is not masking hyperglycemia-induced hemodynamic changes but is instead preventing the changes.…”
Section: Discussionmentioning
confidence: 99%
“…we can conclude from our findings that oxidative stress has probably caused changes in blood flow and forearm vascular conductance in obese children, since the muscle vasodilator response was restored after supplementation with vitamin C 23,24 .…”
Section: Post-interventionmentioning
confidence: 51%